STUDY OF RECTANGULAR MICROSTRIP PATCH OVER GROUND PLANE WITH RECTANGULAR APERTURE USING GALERKIN’S METHOD IN THE VECTOR FOURIER TRANSFORM DOMAIN (Sciences & Technologie. B, Sciences de l'ingénieur, 2004)
In this paper, a rigorous full-wave analysis of rectangular microstrip patches over ground planes with rectangular apertures in substrates containing isotropic and anisotropic materials is presented. The dyadic Green’s functions of the problem are efficiently determined in the vector Fourier transform domain (VFTD). The integral equations for the unknowns patch current and aperture field are solved numerically by applying the Galerkin method of moments. The TM set of modes issued from the magnetic wall cavity model are used to expand the unknown current on the patch. Also, the same basis functions are used for approximating the aperture field in accordance with the concept of complementary electromagnetic structures. The validity of the solution is tested by comparison of computed results with experimental data. Numerical results show that changes in aperture length can drastically shift the resonant frequency. The aperture width, on the other hand, can be used for a fine adjustment of the operating frequency.